'Cropped out': The collaborative production of an accusation of racism. (June 2021) - Rafaely, Daniella
This article utilises the concept of 'race trouble' as an overarching framework for examining an interview between Ms Vanessa Nakate and a South African news broadcaster. The interview describes an incident involving Ms Nakate's attendance at a global climate change conference and her exclusion from a media report about a press briefing that she held along with four other youth activists at the conference. The analysis focuses on the collaborative and interactional production of Ms Nakate's claim that her exclusion was racially motivated and the discursive mechanisms by which race is mobilised as a common-sense explanation for the incident that occurred. My analysis demonstrates the sanctionability of producing an accusation of racism and identifies the rhetorical functions of stake and facticity in its production, and concludes with a discussion of the relevance of these findings in the context of studies on race and racism in interaction.